GIRL-CHILD DISCRIMINATION IN HOMES AMONG SECONDARY SCHOOL STUDENTS IN IKENNE LOCAL GOVERNMENT AREA, NIGERIA (2014)
The World Health Organization states that globally, many girls are denied education, refused health care and exploited both sexually and economically. These negatively influence the health and development of girls. Information on the prevalence of girl-child discrimination is sparse in Nigeria. This study was thus conducted to find out the knowledge of the rights of the girl-child and prevalence of their discrimination among secondary school students in Ikenne Local Government Area (ILGA), Ogun State, Nigeria. A cross-sectional study which utilised quantitative and qualitative research methods was used. A three-stage random sampling technique was used to select 350 students from five of the 17 secondary schools in the LGA. Data on the socio-demographic characteristics and knowledge of the rights of the girl-child were obtained from the students using an interviewer-administered questionnaire. Knowledge was assessed on a 12-point scale. The score was computed and categorized as below average (<6) or above average (? 6). Data on types of discrimination experienced by female students in the three month preceding the study were also obtained. Four Focus Group Discussions (FGDs) were conducted, two each among students and parents. Quantitative data were analyzed using descriptive statistics and Chi-square test while thematic analysis was used for FGD data. Fifty-four percent of respondents were females. Their mean age was 14.0 2.2 years. Almost half (48.4%) of the students reported that their mothers had tertiary education, 42.1% secondary, 5.8% primary and 3.7% had no formal education. The levels of education of their fathers were tertiary (59.2%), followed by secondary (34.4%), primary (4.7%) and no formal (1.7%) education. Majority (97.1%) of students had above average knowledge of the rights of a girl-child. Fourteen percent of boys reported that at least one of their sisters had been discriminated against. About one third (38.5%) of female students reported that they had been discriminated against. Forms of discrimination experienced by female students included restriction from taking part in decision making (59.2%), less attention given when ill (22.4%) and being given less food (18.4%) compared to their brothers. None of the girls had been discriminated against in terms of access to education. A higher proportion of girls whose mothers had no or primary education had experienced discrimination (44.4%) compared with those whose mothers had secondary and higher levels of education (38.2%). More girls (66.7%), whose fathers had no or primary education had experienced discrimination compared with those whose fathers had secondary and higher levels of education (36.8%) (p< 0.05). The FGD revealed that boys and girls were treated differently. Discussants supported survey findings that girl-child discrimination occurred in the community, though covertly and that discrimination took many forms such as being given less food and restriction from the process of decision making compared with boys. Girl-child discrimination occurred in the study area and girls whose parents had primary and no education were more likely to be discriminated against. Interventions to address girl-child discrimination thus need to target all parents especially those with lower levels of education.